THE ANALYSIS OF CONSUMER PREFERENCE ON FEMALE PURCHASE DECISION OF COSMETIC PRODUCTS IN MANADO CITY - Jessica, Paendong Elnike; Pandowo, Merinda (Universitas Sam Ratulangi, 2016)
Globalization is a phenomenon that is leading the entire world towards becoming one market, a global market. It has opened opportunity for local products to enter global market and foreign products to enter local market. Nowadays, there are many various products are assembled come from different countries and they have target market in global market. Beauty product has been viewed as important issue for women because cosmetic is becoming a part of women’s daily life. Women will do anything in order to enhance their appearance and they are very concerned in choosing cosmetic products that they would like to use. There are several factors that affect on purchase decision of cosmetic products. This study aims to analyze the influence of consumer preference towards female purchase decision of cosmetic products in Manado city. This research using quantitative method and multiple regression analysis. The data were gathered from 100 women as the respondents of cosmetic products. This research found that product quality is the strongest predictor towards consumer purchase decision followed by brand image. Country-of-origin and promotion does not have influence on consumer purchase decision of cosmetic products. The marketer should to understand the market segmentation and formulate the competitive marketing strategies and utilize target market properly. Keywords: product quality, brand image, promotion, female purchase decision